Cosmic Muon Detection for Geophysical Applications. (30th April 2013) - Oláh, László; Barnaföldi, Gergely Gábor; Hamar, Gergő; Melegh, Hunor Gergely; Surányi, Gergely; Varga, Dezső
Abstract : A portable cosmic muon detector has been developed for environmental, geophysical, or industrial applications. The device is a tracking detector based on the Close Cathode Chamber, an MWPC-like technology, allowing operation in natural underground caves or artificial tunnels, far from laboratory conditions. The compact, low power consumption system with sensitive surface of 0.1 m 2 measures the angular distribution of cosmic muons with a resolution of 10 mrad, allowing for a detailed mapping of the rock thickness above the muon detector. Demonstration of applicability of the muon telescope (REGARD Muontomograph) for civil engineering and measurements in artificial underground tunnels or caverns are presented.